Testing the Validity of Spatial Beta Convergence for the Countries of Southern Europe - Dora Szendi (Theory, Methodology, Practice)
Territorial economic and social disparities remain a major problem for the European Union today. No two regions have the same characteristics and starting conditions, resulting in significant disparities in their development path. The aim of this study is to analyse the impact of the economic and social shocks of the 2000s (the economic and financial crisis of 2008-09 and the COVID-19 pandemic) on the economies of four countries (Portugal, Spain, Italy and Greece) in Southern Europe. The study presents county-level differences in gross value added and their changes in response to external shocks. The methodology used is based on classical descriptive statistics, convergence analyses (sigma, beta, gamma) and spatial autocorrelation studies. The results show that the impact of the shocks of the 2000s varies across counties, with some areas being able to increase their gross value added even during the crisis period. However, the first and second waves of the economic and financial crisis and the pandemic had an uneven impact on the region's counties, which further increased territorial disparities.